The Future of The Hotel Sector in the Context of Risks Caused by the Pandemic - Bogdan WŁODARCZYK; Krzysztof GRABOWSKI (Communications of International Proceedings, 2024)
The hotel sector is particularly exposed to pandemic risk. This risk has the characteristics of a systematic and random risk, but its impact is focused on the profitability of hotel services. The nature of this risk determines the limited influence of the hotel company on its sources, which means that the time in which losses from this risk are incurred is varied and unpredictable. The purpose of this article is to try to collect and evaluate the conclusions of research on the economic situation and future of hotel enterprises, from the perspective of risks caused by the pandemic. For this purpose, the method of critical analysis of the literature on the subject was used. The results of the study lead to the conclusion that the reduction of losses depends to a large extent on the effectiveness of the measures taken, known as crisis management. As a result, the future of the hospitality sector in particular depends on innovation, organizational culture, the ability to compete and the ability to use modern communication technologies.
Keywords: hospitality sector; risk; economic impact of pandemic